Association of vitamin D deficiency and insufficiency with uncontrolled type 1 diabetes Mellitus among Saudi pediatric patients; a hospital-based retrospective study - Salman Almansour; Abdullrahman Alsalamah; Mohammad Almutlaq; Ahmed Sheikh; Hamdan Z. Hamdan; Abdullah Al-Nafeesah; Ashwaq AlEed; Ishag Adam; Osama Al-Wutayd (Frontiers in Pediatrics)
BackgroundThe association between 25-hydroxy-vitamin D [25(OH)D] levels and glycemic control in pediatric patients with type 1 diabetes mellitus (T1DM) is unclear. In this study, we aimed to investigate the association between 25(OH)D levels and glycemic control in Saudi pediatric patients' with T1DM in a region that is sunny year-round.Materials and methodsA retrospective study was conducted in the Pediatric Department of King Saud Hospital in Unaizah, Saudi Arabia. A total of 218 children with T1DM were enrolled in the study and grouped according to their glycated hemoglobin (HbA1C) levels into the controlled T1DM (HbA1C ≤ 7.5%) and the uncontrolled T1DM (HbA1C > 7.5%). Their 25(OH)D levels and thyroid function were measured using standard methods.ResultsOf the 218 children in this study, 182 (83.5%) had uncontrolled T1DM, while only 36 (16.5%) had controlled T1DM. The median (interquartile range) of 25(OH)D levels was significantly lower in the uncontrolled T1DM group compared with the controlled group [45.4 (31.2–59.7) nmol/L vs. 56.1 (37.5–77.6) nmol/L; p = 0.007], respectively. Vitamin D deficiency (<50.0 nmol/L) and insufficiency (50–74 nmol/L) were detected in 55.0% and 31.1% of all the enrolled children, respectively. Vitamin D deficiency was detected in 86.6% of the uncontrolled T1DM patients and in 16.5% of the controlled T1DM patients (p = 0.012). The multivariable analysis showed that both vitamin D deficiency [adjusted odds ratio (aOR) = 2.92, p = 0.048] and insufficiency [aOR = 3.17, p = 0.042] were risk factors for uncontrolled diabetes.ConclusionVitamin D deficiency was highly prevalent in the studied group. Both vitamin D deficiency and insufficiency are associated with uncontrolled T1DM. Further study is needed.